2018
DOI: 10.1038/s41467-018-07812-8
|View full text |Cite
|
Sign up to set email alerts
|

PI3Kα-regulated gelsolin activity is a critical determinant of cardiac cytoskeletal remodeling and heart disease

Abstract: Biomechanical stress and cytoskeletal remodeling are key determinants of cellular homeostasis and tissue responses to mechanical stimuli and injury. Here we document the increased activity of gelsolin, an actin filament severing and capping protein, in failing human hearts. Deletion of gelsolin prevents biomechanical stress-induced adverse cytoskeletal remodeling and heart failure in mice. We show that phosphatidylinositol (3,4,5)-triphosphate (PIP3) lipid suppresses gelsolin actin-severing and capping activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 75 publications
0
78
0
Order By: Relevance
“…It has been demonstrated that the gelsolin‐PI3Kα (p110α) complex plays an important role in the regulation of gelsolin function in cytoskeletal remodeling (Patel et al, ). Therefore, we next investigated the effect of NA treatment on the gelsolin‐PI3Kα (p110α) interaction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that the gelsolin‐PI3Kα (p110α) complex plays an important role in the regulation of gelsolin function in cytoskeletal remodeling (Patel et al, ). Therefore, we next investigated the effect of NA treatment on the gelsolin‐PI3Kα (p110α) interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that PI3Kα inhibits gelsolin activity by converting PIP2 to PIP3, and actin filament assembly could be functionally rescued with PIP3 through activating gelsolin in cardiomyocytes (Patel et al, ). Our results showed that NA treatment significantly inhibited the interaction between PI3Kα (p110α) and gelsolin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, PI3Kα activity protects the heart against myocardial infarction‐induced heart failure [191], can improve the function of a failing heart, is important for exercise‐induced cardioprotection [192], and can protect against heart disease in response to dilated cardiomyopathy and acute pressure overload [193,194]. PI3Kα also negatively regulates gelsolin‐activity to suppress gelsolin's actin‐severing activity that contributes to cardiac remodelling in heart failure [195]. PI3Kα's role in mediating insulin signalling to L‐type calcium channels to regulate calcium currents in cardiac myocytes is a key mechanism underpinning the importance of this Class I PI3K isoform in the heart, while both PI3Kα and PI3Kβ support cardiac structure and organisation via regulation of junctophilin‐2 localisation and T‐tubule organisation [152, 196, 197].…”
Section: Pi3ks In Other Aspects Of Cardiovascular Diseasementioning
confidence: 99%